2016
DOI: 10.1111/bcp.13176
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of intrathecally administered Xen2174, a synthetic conopeptide with norepinephrine reuptake inhibitor and analgesic properties

Abstract: At the Xen2174 dose level of 2.5 mg, CSF concentrations exceeded the prespecified exposure limit based on the nonclinical safety margin. No statistically significant effects on evoked pain tests were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The present study adds to a body of research studies in which this exact battery of evoked pain tasks was used to investigate various analgesic compounds alone (Okkerse et al., ,c,d) or combined (Okkerse et al., ). As such, the battery of evoked pain tasks is pharmacologically validated for the effects of cannabinoids and sedatives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study adds to a body of research studies in which this exact battery of evoked pain tasks was used to investigate various analgesic compounds alone (Okkerse et al., ,c,d) or combined (Okkerse et al., ). As such, the battery of evoked pain tasks is pharmacologically validated for the effects of cannabinoids and sedatives.…”
Section: Discussionmentioning
confidence: 99%
“…Pain detection and tolerance thresholds were measured using a battery of evoked pain tasks, as described previously (Hay et al., ; Okkerse et al., ,b,c,d). The test battery consists of an integrated range of pain tasks for measuring different modalities of pain.…”
Section: Methodsmentioning
confidence: 99%
“…Xen2174 (χ-CTX MrIA from C. marmoreus ) progressed to Phase IIb trial ( Lewis, 2015 ), but it showed dose-limiting toxicity in pharmacodynamics and cerebrospinal fluid pharmacokinetics assays. Thus, it is unlikely that this conotoxin can be used for the treatment of acute pain in humans ( Okkerse et al., 2017 ).…”
Section: Learning From Discontinued Toxin-based Drugsmentioning
confidence: 99%
“…Xen2174 was licensed to Xenome Ltd and entered various stages of clinical trials for the treatment of cancer and post-surgical pain [68]. A recent publication on the pharmacodynamics and the cerebrospinal fluid pharmacokinetics of Xen2174 in healthy patients concluded that no statistically significant effect on evoked pain was observed [69]. Additionally data from previous clinical studies provided no conclusive results on the analgesic properties of Xen2174 in humans [69] suggesting that this peptide drug does not exhibit sufficient efficacy for the treatment of pain in humans.…”
Section: Mria An Inhibitor Of the Norepinephrine Transporter (Net) Wmentioning
confidence: 99%